Indeks Luas Daun Berbagai Umur Dan Jumlah Bibit Tanaman Padi (oriza sativa. L) Dalam Optimalisasi Jumlah Anakan - Gamawati Adinurani, Praptiningsih; Rahayu, Sri; Santoso, Teguh (JURNAL AGRI-TEK, 2017)
Seedlings that are less appropriate at the time of planting move will affect the stagnation of growth and impact on the preparation of leaf chlorophyll for photosynthesis. The purpose of research to determine the number of tillers at leaf area index of various ages of move planting and the number of seedlings per plant (Oryza sativa L). The study used a split-plot design. The main plot was the number of seedlings per plant (1, 3, 5), sub-plot was seed age factor (dry seedlings 15 HSS, dried seedlings 18 HSS, wet seedlings 20 HSS and wet seedling 24 HSS). The result of a study showed that various of seed age were significantly different on leaf area but not significantly different on leaf area index. The number of seedling per plant were significantly different on leaf area and leaf area index. Average of plant height of wet seedling (96.71 cm) more high than dry seedlings (87.27 cm) but the increasing of plant height of dry seedlings (68.24 %) more than wet seedlings (57.29 %). There was significant interaction between various age of move planting and number of seedling at number of tillersKeywords: chlorophyl, rice, seed number per plant, seedling age, dry seedlings, wet seedlings